The Relationship Between Response Time and The Effect of Hospitalization on Preschoolers - Abidah, Nurul Zakiyah; Zuhroh, Diah Fauzia; Eka, Diah Jerita (Universitas Muhammadiyah Gresik, 2024)
Objective : Response time is the speed of health workers in treating patients starting from the time the patient comes to the emergency room until he gets health care . The indicator of success is the speed of officers in providing assistance to emergency patients ≤ 5 minutes. One of the first units to go to at the hospital is the emergency room. In children, not all treatments given are acceptable and even these treatments can have an impact or effect on the child's hospitalization. This study aims to analyze the correlation between response time and the effect of hospitalization on preschool children in the emergency room of the Muhammadiyah Gresik hospital. Methods : This type of research is analytic with a cross-sectional approach with a patient population of preschool children (3-6 years) who come to the emergency room of the Muhammadiyah Gresik hospital with a total of 132 children as respondents. And using purposive sampling method. Data analysis in this study used the Chi-Square test to determine the relationship between response time and the effect of hospitalization on preschool children with a significant p value = <0.05. Results : Preschoolers children in the emergency room of Muhammadiyah Gresik hospital Most (54.5%) experienced the effects of anxious hospitalization, namely as many as 72 children. Response time of nurses to preschool children in the emergency room of the Muhammadiyah Gresik hospital, almost all of them were fast (89.4%), namely 118 children.. Conclusion : There is no correlation between response time and the effects of hospitalization in preschool children with a p-value = 0.056 Keywords: Hospitalization Effect, Response Time